Analysis of the Influence Factors of ULP Service Quality on PPK Satisfaction in the Electronic Selection Process of Government Goods or Services Providers in Bandung City - Iqlima, Ulfa; Rachmat, Agus; Kadir, Yushar (Journal of Current Research In Multidisciplinary, 2024)
Electronic Procurement Services (LPSE) aim to support transparent, efficient, and accountable government procurement of goods and services. This study assesses the satisfaction of Commitment Making Officers (PPK) with the services of the Bandung City Procurement Service Unit (ULP) using a descriptive analytical method. We collected data using a questionnaire that measured variables such as reliability, responsiveness, assurance, empathy, and tangibles. The results of the study showed that the PPK satisfaction index was in the satisfied category, with several aspects, such as speed of service and competence of ULP workers, being the dominant indicators. However, the study identified several weaknesses, such as inadequate two-way communication and insufficient physical facilities. This study provides recommendations for improving ULP services by strengthening communication, providing more adequate facilities, and offering ongoing workforce training. This study aims to improve the quality of electronic procurement of goods and services in Bandung City, thereby fostering better governance.